Vit D Status and Osteoporosis in Tobacco Consuming Men in Rural Region Surrounding Wardha City, Maharashtra, Central Part of India - Ajay Meshram1 , Komal Meshram1 , Ranjeet Ambad2 , Karuna Kacchua3 , Lata Kanyal5 , Shilpa Ingle4 , A (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Awareness towards tobacco consumption has increased and it is well accepted too but will ithelp to cease the consumption. With widespread menace of tobacco consumption in developing country likeIndia, not much data of study is available currently about tobacco consumption and osteoporosis around therural region of Wardha a central part of India.Aim: Vit D status and osteoporosis in tobacco consumers and non consumers.Objective: To asses influence of tobacco consumption on Sr. Vit D, Sr. ionized Ca, Sr. Phosphate, Sr.parathyroid hormones the biochemical markers of bone turnover and Bone mineral density in a cohort of214 healthy men in rural area surrounding Wardha region of Maharashtra.Design: A cross sectional studySubjects: 214 healthy men aged around 30-50 years with no disease history were included in the study.Results: Tobacco consumers had significantly reduced levels of Sr 25 OH Vit D (P<0.02), PTH (P<0.001).There was no significant difference in Sr ionized Calcium between tobacco consumers and Non tobaccoconsumers. We got negative effect of tobacco consumption on Sr Osteocalcin (P<0.01).Conclusion: Calcium and Vit D metabolism is significantly deranged by habit of tobacco consumption andcannot be explained by life style factors. Vitamin D- PTH system depression among tobacco consumersrepresent a other mechanism for the deleterious effects of tobacco consumption on the bones and contributeto reported risk of osteoporosis among tobacco consumers.Sponsorship: Intra mural Grant from DMIMS(DU)